Analysis of ECG Measures of Cardiac Repolarization in Relation to Arrhythmic Events in an Implantable Cardioverter Defibrillator Population. Issue 2 (13th June 2016) - Shi, Bijia; Harding, Scott; Larsen, Peter
Abstract : Background: ECG‐derived measures of cardiac repolarization may have utility in risk prediction of future ventricular arrhythmia, and a range of different measures have been proposed. We compared time‐based, vectorcardiographic, and singular value decomposition (SVD) derived measures of repolarization to determine which was most predictive of appropriate therapy in an ICD population. Methods: We examined the independent prognostic value of a range of repolarization measures derived from 60 second 12‐lead ECG recordings in 150 patients receiving new ICD implants in relation to the occurrence of appropriate therapy during follow‐up. Results: Over an average follow‐up of 2.15 ± 0.87 years, male gender, presence of premature ventricular complex (PVC), relative T wave residuum (TWR‐rel, measures regional repolarization heterogeneity), and TCRT (the total cosine R‐to‐T, describes the global angle between repolarization and depolarization wavefronts) were the only independent predictors of appropriate therapy. With every 0.01% increase in TWR‐rel, there was 2% increased risk of appropriate therapy (HR = 1.02, 95% CI 1.006–1.034, P < 0.001). With every 1° decrease in TCRT, there was an increase in arrhythmic risk of 0.9% (HR 1.009, 95% CI 1.003–1.015, P = 0.003). Conclusions: The use of advanced analytic ECG techniques to derive measures of repolarization abnormality might shave utility in risk stratification in an ICD population.